Women’s Language In Media: A Study Of Blackpink’s Interview On Zach Sang Show Podcast - Nazmi Fawwaziah; Abd. Hannan; Hasbi Assiddiqi (Hasanuddin University, 2026)
This study examines women’s language features in global media discourse by analyzing Blackpink’s interview on the Zach Sang Show podcast. It explores how Lakoff’s theory operates in the context of multilingualism and global celebrity status. Using a descriptive qualitative method, data were collected from the transcription of Blackpink’s 2019 podcast interview and analyzed using Lakoff’s framework, and the stages of data condensation, data display, and conclusion drawing proposed by Miles, Huberman, and Saldaña (2014). The findings show that eight out of ten women’s language features were identified in the conversation. Lexical hedges and fillers appeared most frequently (36%), while the second most frequently intensifiers (32%). And rising intonation, empty adjectives, precise color terms, super polite form, avoidance of strong swear words, and emphatic statement occurred less frequently. These results suggest that women’s language features function as strategic linguistic choices shaped by multilingualism and celebrity identity. By integrating Lakoff’s theory to global media and celebrity discourse, this study contributes to the development of sociolinguistic research.